(untitled) (Anclajes, 2025)
In 1833, a gauchesco dialogue was published in Portuguese in the Porto Alegre newspaper O Recopilador Liberal. It is an extemporaneous appearance, since it oc curred at a date prior to what is considered to be the emerging moment of gauchesca literature in Rio Grande do Sul (the 1870s). Through the joint analysis of the piece by O Recopilador Liberal with a corpus of Rioplatense gauchescos dialogues (by Bartolomé Hidalgo and Hilario Ascasubi), the singularities of Brazilian composition are revealed in terms of the way of constructing the gauchesco locution device. Unlike what happens in the conversations composed on the Spanish side of the border, in the dialogue that ap peared in the Porto Alegre newspaper, the gaucho’s speech is subsidiary to the master’s speech, thus constructing a relationship of heteronomy that compromises the plebeian perspective that, in principle, the gauchesco genre establishes.